Dysphagia As a Clinical Manifestation of Esophageal Achalasia: A Case Report - Elizabeth, Elizabeth; Nurhikmah, Siti (Jurnal Ners, 2024)
Esophageal achalasia is a disorder of esophagus movement which characterized by lack or absence of esophageal peristalsis and the inability to relax either partially or totally in the lower esophageal sphincter. Esophageal achalasia is a rare case of the disease, the case occurrence rate is 1:100.000 population with a prevalence of 10 per 100.000. The main symptom marker of esophageal achalasia is dysphagia. Accompanied by other symptoms such as regurgitation, cough after eating, nausea, vomiting, weight loss, burning sensation, substernal pain in the early stages and epigastric pain in the advanced stage. A 65-year-old woman patient presented with difficulties in swallowing for approximately 2 months. The results of blood laboratory tests obtained leukocytosis, thrombocytosis and decreased of platelet distribution width (PDW). On electrolyte examination found hyponatremia, hypokalemia and decreased blood chloride. The results of the barium esophagogram examination found narrowing in the distal part of esophagus that resembles the rat’s tail appearance. The patient was diagnosed with esophageal achalasia and referred to another hospital for definitive surgical therapy.